Factors affecting workplace happiness in Majlis Perbandaran Pasir Gudang (MPPG) / Afi Azyan Rohaizat - Rohaizat, Afi Azyan (Faculty of Business and Management, 2020)
The purpose of this paper is to identify the factors affecting workplace happiness. The factors that have been discussed in this research are leadership, relationship with colleagues and income. There are three research questions for this research paper. Firstly, what is the relationship between leadership and workplace happiness? Next, what is the relationship between the relationship among colleagues and workplace happiness? Lastly, what is the relationship between income and workplace happiness? The objectives of this research are to examine the relationship between leadership/relationship with colleagues/income and the workplace happiness. This paper provides a comprehensive framework that contributes to the conceptualization of factors affecting workplace happiness. This research is a descriptive research; correlational, non-contrived which involved field study with minimal researcher, cross sectional and the unit of analysis is the individual. The researcher used a non-probability sampling which is convenience sampling to collect the data. In this research, there is a significant, positive and moderate correlation between leadership/relationship with colleagues/income and the workplace happiness.